The Effect of Neuromodulatory Drugs on the Intensity of Chronic Pelvic Pain in Women: A Systematic Review - Andrade, Marcela Almeida; Soares, Leila Cristina; Oliveira, Marco Aurélio Pinho de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective: To evaluate the effect of neuromodulatory drugs on the intensity of chronic pelvic pain (CPP) in women.Data sources: Searches were carried out in the PubMed, Cochrane Central, Embase, Lilacs, OpenGrey, and Clinical Trials databases.Selection of studies: The searches were carried out by two of the authors, not delimiting publication date or original language. The following descriptors were used: chronic pelvic pain in women OR endometriosis, associated with MESH/ENTREE/DeCS: gabapentinoids, gabapentin, amitriptyline, antidepressant, pregabalin, anticonvulsant, sertraline, duloxetine, nortriptyline, citalopram, imipramine, venlafaxine, neuromodulation drugs, acyclic pelvic pain, serotonin, noradrenaline reuptake inhibitors, and tricyclic antidepressants, with the Boolean operator OR. Case reports and systematic reviews were excluded.Data collection: The following data were extracted: author, year of publication, setting, type of study, sample size, intervention details, follow-up time, and results.Data synthesis: A total of 218 articles were found, with 79 being excluded because they were repeated, leaving 139 articles for analysis: 90 were excluded in the analysis of the titles, 37 after reading the abstract, and 4 after reading the articles in full, and 1 could not be found, therefore, leaving 7 articles that were included in the review.Conclusion: Most of the studies analyzed have shown pain improvement with the help of neuromodulators for chronic pain. However, no improvement was found in the study with the highest statistical power. There is still not enough evidence that neuromodulatory drugs reduce the intensity of pain in women with CPP.
Keywords: chronic pelvic pain; management; neuromodulations drugs; gabapentin; sertraline